Theoretical-practical theology - Mastricht, Peter van., 1630-1706 (Grand Rapids, Michigan.: : Reformation Heritage Books, 2018)
"An English translation of Petrus van Mastricht's Theoretico-Practica Theologia, which presents a system of Reformed theology in its exegetical, doctrinal, elenctical, and practical parts"--
Volume 1. Prolegomena
"An English translation of Petrus van Mastricht's Theoretico-Practica Theologia, which presents a system of Reformed theology in its exegetical, doctrinal, elenctical, and practical parts"-- Provided by publisher.
Keywords: Reformed Church -- Doctrines -- Early works to 1800.